2023
DOI: 10.7759/cureus.43513
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology and Clinical Features of Lymphangioleiomyomatosis (LAM): A Descriptive Study of 33 Case Reports

Jaini M Shah,
Jaimin T Patel,
Hriday Shah
et al.

Abstract: Lymphangioleiomyomatosis (LAM) is a rare, slow-growing metastasizing neoplasm in which smooth muscle-like cells infiltrate the lung parenchyma and cause cystic lung damage. The common early symptoms include shortness of breath, pneumothorax, and chest pain. Lymphangioleiomyomatosis mainly involves the lungs, kidneys, and lymph nodes. This study reviews the characteristics of lymphangioleiomyomatosis to identify any possible changes in the prevalence of symptoms of the disease. We conducted a literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…LAM may occur as an isolated disease or coexist with tuberous sclerosis (TSC) [1,3]. The incidence of sporadic lymphangioleiomyomatosis (S-LAM) is unknown, but one study found that the sporadic form occurs in 1 in 400,000 adult women [4]. The sporadic form of LAM (S-LAM) is due to an acquired mutation, mainly in the TSC2 gene [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…LAM may occur as an isolated disease or coexist with tuberous sclerosis (TSC) [1,3]. The incidence of sporadic lymphangioleiomyomatosis (S-LAM) is unknown, but one study found that the sporadic form occurs in 1 in 400,000 adult women [4]. The sporadic form of LAM (S-LAM) is due to an acquired mutation, mainly in the TSC2 gene [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…These are cases with no other TSC symptoms. Unlike S-LAM, which mainly affects women, tuberous sclerosis complex lymphangioleiomyomatosis (TSC-LAM) affects both men and women with TSC [4]. The hereditary form of LAM (TSC-LAM) affects about 40% of patients with tuberous sclerosis (TSC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microscopically, LAM is distinguished by abnormal hyperplasia of smooth muscle cells in the lungs, lymphatic vessels, and mediastinal, abdominal, and lower cervical lymph nodes (3). The primary site of occurrence is the lungs, most patients experience pulmonary symptoms, including pneumothorax, chest pain, cough, and pleural effusion (4). Despite the rarity of extrapulmonary LAM, instances have been reported in the mediastinum and retroperitoneum, often accompanied by pulmonary invasion.…”
Section: Introductionmentioning
confidence: 99%